Pertanggungjawaban Pidana Atas Maraknya Tindak Penipuan Vaksinasi Covid-19 Melalui SMS di Indonesia - Yvonny Yvonny; Abdurrakhman Alhakim (Universitas Batanghari Jambi, 2022)
Development of sophisticated information technology in addition to facilitating community activities, also has bad impact to human’s behaviour, one of them is using technology to commit crimes by disseminating incorrect information related to Covid-19 vaccination using mobile phones via Short Message Service. This is stated to have been experienced by many people in Indonesia, so that is why the problem must be immediately addressed legally for the security of people's personal data. This research aims to know about criminal liability for perpetrators of fraudulent Covid-19 vaccination via SMS in Indonesia and legal protection to victims of the criminal act of fraudulent Covid-19 vaccination via SMS in Indonesia. The problems in this research is examined using normative research methods that analyzed qualitatively descriptively using secondary data from primary, secondary, and tertiary legal materials. Result of this research is indicate that the legal rules regarding fraudulent acts of disseminating information through telecommunication media are applied in Indonesia, so it is necessary to update stricter legal rules for perpetrators of fraudulent acts of spreading hoax information via SMS, so victims who experienced that problem will get proper legal protection.